Creating a Warmer Environment for Women in the Mathematical Sciences and in Philosophy - Brennan, Samantha; Corless, Rob (Atlantis, 2009)
Speaking from our experience as department chairs in fields in which women are traditionally underrepresented, we offer reflections and advice on how one might move beyond the chilly climate and create a warmer environment for women students and faculty members.